Pameran Arsip Virtual pada Lembaga Kearsipan sebagai Upaya Peningkatan Penjangkauan Kearsipan: Studi Kasus di Arsip Nasional Republik Indonesia - Tri Yekti Mufidati; Tamara Adriani Salim (Khazanah: Jurnal Pengembangan Kearsipan, 2023)
This research discusses the holding of virtual archives exhibitions as an effort to increase archival outreach at the National Archives of the Republic of Indonesia (ANRI) as an archival institution and relevant to ANRI's function in managing archives (historical value archives). The purpose of this study is to describe the holding of a virtual archives exhibition by ANRI as an effort to increase archival outreach by ANRI. This research uses a qualitative approach with a case study method, data collection is carried out by making observations, interviews, and document analysis. Data gathering of this study was conducted from February 2021 to May 2022.  The results of this study show that the holding of a virtual archive exhibition at ANRI as an innovation in archives management supported by policies in regulating the stages of organizing, managing exhibition resources, collaboration and sustainability of virtual archive exhibitions will support efforts to increase archival outreach. The virtual archives exhibition is held in accordance with ANRI's vision and mission in managing archives as a collective memory and national identity by utilizing social media platforms websites, Instagram, YouTube, Twitter, and Facebook. With the use of social media in organizing a virtual archive exhibition by ANRI, it can reach a wider range of archives users.